Aneuploidies in older women, what are the actual risks? - Valdez León, Federico Javier (2014)
Over the last decades, there has been a clear tendency in couples planning to have children later in life. Better educational and career opportunities and broad availability of contraception have been some of the contributing factors in couples postponing the beginning of a family. Advanced maternal age (AMA) is currently considered the main risk factor for chromosome aneuploidies, but there is no exact number as to the probability of actually producing aneuploid embryos or a mayor reason for this to happen. The object of this review is to address the recent findings and to near down the probability of actually producing aneuploidy embryos in AMA women. Also we will try to elucidate the actual reason as to why this is happening and how it is related to the age of the mother. We hope these findings will help couples that are thinking about starting a family and couples that are starting or thinking about IVF treatment.